Summer secrets [large type] : a novel - Green, Jane, 1968- (Thorndike Press Large Print, 2015)
When a shocking family secret is revealed, twenty-something journalist Cat Coombs finds herself falling into a dark spiral. Wild, glamorous nights out in London and raging hangovers the next day become her norm, leading to a terrible mistake one night while visiting family in America, on the island of Nantucket. It's a mistake for which she can't forgive herself. When she returns home, she confronts the unavoidable reality of her life and knows it's time to grow up. But she doesn't know if she'll ever be able to earn the forgiveness of the people she hurt. As the years pass, Cat grows into her forties, a struggling single mother, coping with a new-found sobriety and determined to finally make amends. Traveling back to her past, to the family she left behind on Nantucket all those years ago, she may be able to earn their forgiveness, but in doing so she may risk losing the very people she loves the most. Told with Jane Green's keen eye for detailing the emotional landscape of the heart, Summer Secrets is at once a compelling drama and a beautifully rendered portrait of relationships, betrayals, and forgiveness; about accepting the things we cannot change, finding the courage to change the things we can, and being strong enough to weather the storms.